(untitled) (Acta Polytechnica CTU Proceedings, 2017)
The aim of this paper is to evaluate soil shear strength from the Dobkovicky landslide. The landslide was activated on June 6, 2013 after heavy rains and the D8 motorway, which was under construction at the time, was damaged. The laboratory tests were carried out on two types of soils, clay and tuff, both from the surface of the rupture. Critical and residual friction angles were evaluated on both types of soils.